Disaster risk reduction in the livestock sector: the Costa Rican experience - Díaz, Alejandra (United Nations Office for Disaster Risk Reduction (UNDRR), 2022)
This report explores those actions and the National Program on Animal Management in Disasters. The report also evaluates the context of risk in Costa Rica’s livestock sector, as well as the governance of and agenda for risk management. Moreover, the authors analyze economic losses and investments in animal care in disasters, lessons learned from different institutions’ experiences and framework implementation processes, and challenges and opportunities for improvement.